Debt capital markets in China - Gao, Jian (John Wiley & Sons, 2007)
Author Jian Gao is the number one authority on fixed income markets in China, and with this book, he brings his considerable experience and knowledge about these markets to investors worldwide. For those interested in becoming active in China’s growing fixed income markets, Debt Capital Markets in China is the book you need to get started. It includes coverage of the primary and secondary markets, government debt instruments, corporate bonds, the collateralized bond market, and asset-backed securitizations. Debt Capital Markets in China also examines the developing market trends, which affect investors and institutions looking to make the most of this incredible financial opportunity.